Determining appropriate provinces for dew harvesting in Iran - mehdi sarparast; muosa hesam; hamidraza asgari (Environmental Resources Research, 2014)
The fact that water is the most important factor of life on earth is not a new concept. Alteration and reduction in the amount of precipitation, population explosion and contamination of underground water pressurize governments severely to find solution for water resources. The air moisture is one of fresh water resources which has not been noticed and well exploited. In this study proper places were identified for dew harvesting in Iran based on three important aspects: relative humidity, wind speed and the number of sunny days. The province centres was considered as a whole indicator. Areas with an average relative humidity of more than70%, wind speed less than 3m/s and the sunny days were the best sites for dew harvesting. Based on comparisons and available maps generated from Arc-GIS software, the Coastal provinces in north and south of Iran including Golestan, Mazandaran, Gilan, Bushehr and Hormozgan whichcomprise about 17% of the total area of the country were identified to be suitable for this purpose. However Bushehr and Hormozgan provinces were mostly suitable compared to others regions due to extended sunny days.